Ser criança em uma escola pública do lado brasileiro da fronteira Brasil/Paraguai: dos feixes atando pontes - Godoy, Marisa Elizabete Cassaro (2015)
This dissertation aims to present children's perceptions of the school and the neighborhood they live located by the banks of the Parana River in Foz do Iguaçu. Although this context brings on to unique forms of life for all border residents of the three countries, our interest in children of the fifth grade of elementary school focuses on their perceptions of the place where they live, characterized by the gathering of several load activities of goods coming from Paraguay. The child, understood through the theoretical contributions of the child and childhood anthropology, is seen as an actor in social constitutions and also as producer of culture. Under an interdisciplinary perspective, the research was conducted in a public school, through ethnographic research and psychology and educational psychology proper techniques, so that the children could make drawings and, with them, express their life story. One of the perceptions pointed that being a child, in that neighborhood, is living under mistrust looks and experiencing mixed feelings when referring to the adults job, but also undergoing feelings of care and protection of those adults towards them. Residents, in those children s perception, are not smugglers, or muambeiros as called by locals, neither the bosses nor "chiefs" of the network that loads goods, and don t even buy them.